2018
DOI: 10.1177/0194599818803305
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Racial Disparities in Infant Hearing Loss

Abstract: Objective: Approximately 1-2 of every 1000 American newborns has hearing loss identified by newborn screening. This study was designed to determine if infant hearing loss is more common in socioeconomically disadvantaged communities. Study Design: In this retrospective study we analyzed electronic medical record data using geostatistical models. Setting: Infants were residents of Durham County, NC, born in two hospitals of the Duke University Health System. This county includes the city of Durham and surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 15 publications
(38 reference statements)
3
29
0
1
Order By: Relevance
“…(40,54,56,57) The importance of understanding how socioeconomic factors affect the utilization of and access to the healthcare system is becoming increasingly evident. The role of a patient's social and economic circumstances in their overall physical and mental health has been well-elucidated (3,11,31,45,47,52,(57)(58)(59), and our findings are consistent with a limited number of previous studies in documenting an association between socioeconomic status and patient satisfaction scores. caring for patients with, or working in areas with, high levels social deprivation.…”
Section: Resultssupporting
confidence: 90%
“…(40,54,56,57) The importance of understanding how socioeconomic factors affect the utilization of and access to the healthcare system is becoming increasingly evident. The role of a patient's social and economic circumstances in their overall physical and mental health has been well-elucidated (3,11,31,45,47,52,(57)(58)(59), and our findings are consistent with a limited number of previous studies in documenting an association between socioeconomic status and patient satisfaction scores. caring for patients with, or working in areas with, high levels social deprivation.…”
Section: Resultssupporting
confidence: 90%
“…The importance of understanding how socioeconomic factors affect the utilization of and access to the healthcare system is becoming increasingly evident. The role of a patient's social and economic circumstances in their overall physical and mental health has been well-elucidated(3,11,31,45,47,52,(57)(58)(59), and our findings are consistent with a limited number of previous studies in documenting an association between socioeconomic status and patient satisfaction scores.Young et al demonstrated that average income levels based on zip codes and lower patient satisfaction scores are correlated among elderly patients seen in various specialty clinics (60). McFarland et al evaluated 934,000 patients and showed Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey scores were directly correlated with education level, which has been used as a surrogate for socioeconomic status in the literature (38).…”
supporting
confidence: 90%
“…ADI is a composite index that draws from several weighted indicators of neighborhood socioeconomic disadvantage, including constructs of income, employment, education and housing quality [15]. ADI is validated at the neighborhood level and has been used in several other studies [16][17][18].…”
Section: Data Source and Cohort Creationmentioning
confidence: 99%